Pendampingan Kelompok Peternak Lebah Trigona: Pengayaan Pakan Dengan Pola Agroforestri Di Desa Rompegading Kabupaten Maros - Sitti Nuraeni; Budirman Bahtiar; Andi Detti Yunianti; Baharuddin Baharuddin; Ira Taskirawati; Nurfadilah Latif; Andi Prastiyo; Marwan Rajab (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: The potential for the development of meliponiculture in and around the Unhas Bengo-Bengo Educational Forest (BEF) can be an alternative business from non-timber forest resources. The have already occupied of part of the community in the BEF area requires an understanding of the benefits of the forest and community empowerment through community service activities. One effort to understand is how to enrich bee feed which integrates meliponiculture and agricultural crop cultivation with agroforestry patterns. The implementation of this activity starts with preparation by entering into agreements with the service team with partners, conducting workshops, distributing plant seeds as a source of nectar and pollen feed. The knowledge of partner group members can increase after attending the workshop from the pre test and post test analysis. Assistance is provided through direct visits to the location of meliponiculture and planting of nectar and pollen source plants.  Keywords: agroforestry pattern; feed enrichment; Stingless bee trigona Abstrak: Potensi pengembangan budidaya lebah trigona di dalam dan sekitar Hutan Pendidikan Bengo-Bengo (HPB) Unhas dapat menjadi usaha alternatif dari sumber daya hutan bukan kayu. Keterlanjuran sebahagian masyarakat berada dalam kawasan HPB mengharuskan perlu diberi pemahaman manfaat hutan dan pemberdayaan masyarakat melalui kegiatan pengabdian kepada masyarakat. Salah satu upaya pemahaman adalah bagaimana pengayaan pakan lebah yang mengintegrasikan budidaya lebah madu trigona dan budidaya tanaman pertanian dengan pola agroforestri. Pelaksanaan kegiatan ini dimulai dari persiapan dengan melakukan kesepakatan tim pengabdian dengan mitra, pelaksanaan workshop, pembagian bibit tanaman sebagai sumber pakan nektar dan polen. Pengetahuan anggota kelompok mitra dapat meningkat setelah mengikuti workshop dari analisis tes awal dan akhir. Pendampingan dilakukan melalui kunjungan langsung ke lokasi meliponikultur dan penanaman tanaman sumber nektar dan polen.   Kata kunci: lebah madu trigona; pengayaan pakan; pola agroforestri